Similarities and Differences in Theme, Character, Setting, Plot, and Point of View of the Jatisaba Novel and the Bekisar Merah Novel - Utomo, Tirto Aji; Nuryatin, Agus (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Elements are important parts of a literary work. An element functions to build a framework in a literary work, for instance, the character element contained in the Bekisar Merah novel by Ahmad Tohari. The main character in this novel is a female. Her name is Lasi. A female main character is also found in the Jatisaba novel by Ramayda Akmal. Her name is Maemunah. It shows that the element in the Bekisar Merah novel and the Jatisaba novel is similar. This element is especially in the aspect of the character. The objective of this study is to find out similarities and differences related to the elements contained in the Jatisaba novel and the Bekisar Merah novel. An intertextual and a structural approach were applied in this study. The data were collected through structural methods and semiotic reading methods. The data in this study are in the form of fragments of text of the Jatisaba novel and the Bekisar Merah novel. Data analysis was carried out by using structural methods and semiotic methods. The results show that there are similarities related to the elements between the two novels. These elements include theme, character, setting, and plot. In addition, there are also differences between the two novels related to the theme, character, setting, and point of view. This research is beneficial for the community to find out the relationship between novels.